Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Hooke's Law and Simple Harmonic Motion

  1. Dec 11, 2004 #1
    We did an experiment with a vertical spring-mass system. Here is an example of data collected:
    Mass------------T (period)
    200 g-----------.3 s
    400g------------.5 s

    My question is why does the period increase as the mass increases?

    I know that the amp. and T are independent of each other, but how do you show this mathematically? I now it’s easy to show visually, but are there any ties in deriving this, along with the relationship that T = 1/sqrt(x)?

    Then, my teacher mentioned some of the following derivisions. I understand a majority of it, but I don’t know how these two parts directly correspond with each other. Does this look familiar to anyone? I don’t quite follow the M_efficiency line, but I do get the calculus.
    1st Part
    F = -kx, where T = 2*pi*sqrt(M/k) and Mg = kL (L=x)
    M*[(d^2*x)/(dt^2)] = -(k/M)x (second derivative)
    (d^2*x)/(dt^2) = -w^2*x, where w (or omega) = 2*pi*f
    x(t) = Asin(wt + phi)
    This is to show that T is proportional to k, I guess.

    2nd Part
    M_efficiency = M + (M_spring/3)

    k_spring = (1/2) integrate(dx/dt)^2 dm

    v/L = (dx/dt)/x
    mass density p = dm/dx, where p = M_spring/L, where L is length
    k_spring = (1/2)*definite integral(xv/L)^2 pdx L to 0
    k_spring = ½*[(pL^3v^2)/(3L^2)] = ½*(M_spring/3)v^2

    and somehow KE = ½[M + (M_spring/3)]*v^2. How do you get to this point?

    Thanks for ANY help.
  2. jcsd
  3. Dec 11, 2004 #2
    I dont know about M efficiency or whatever.
    But the period proportional to the mass is pretty simple to explain.

    F = m\ddot{x} = -kx


    \ddot{x} + \frac{k}{m}x = 0\ \ \ \ (1)

    now you know that x itself is a function and can be modelled as:

    x = A \cos ( \omega t + \phi )

    taking the first derivative gives you:

    \dot{x} = -A\omega \cos ( \omega t + \phi )

    the second derivative gives you:

    \ddot{x} = -A\omega ^2 cos ( \omega t + \phi )

    notice that's also equal to:

    \ddot{x} = - \omega ^2 x

    substituting this in equation (1) gives you:

    -\omega ^2x + \frac{k}{m}x = 0

    Solving for omega gives you

    \omega = \sqrt{\frac{k}{m}}

    so the period will equal to:

    T = 2\pi \sqrt{\frac{m}{k}}
  4. Dec 12, 2004 #3
    Should be [tex]\dot{x} = -A\omega \sin (\omega t + \phi)[/tex].
  5. Dec 12, 2004 #4
    Could you explain the first line before Equation 1? How did you get from that line to Equ(1)?

  6. Dec 12, 2004 #5


    User Avatar
    Homework Helper

    He got that line by simply applying Newton's 2nd Law (For Constant Mass).

    [tex] \sum_{i=1}^{n} \vec{F}_{i} = m \vec{a} [/tex]
  7. Dec 12, 2004 #6
    Is there a relationship between displacement and period? How do I go about showing this mathematically?

Share this great discussion with others via Reddit, Google+, Twitter, or Facebook